A Benzimidazole Proton Pump Inhibitor Increases Growth and Tolerance to Salt Stress in Tomato - Van Oosten, Michael J.; Silletti, Silvia; Guida, Gianpiero; Cirillo, Valerio; Di Stasio, Emilio; Carillo, Petronia; Woodrow, Pasqualina; Maggio, Albino; Raimondi, Giampaolo (Frontiers in Plant Science, 2017)
Pre-treatment of tomato plants with micromolar concentrations of omeprazole (OP), a benzimidazole proton pump inhibitor in mammalian systems, improves plant growth in terms of fresh weight of shoot and roots by 49% and 55% and dry weight by 54% and 105% under salt stress conditions (200 mM NaCl), respectively. Assessment of gas exchange, ion distribution and gene expression profile in different organs strongly indicates that OP interferes with key components of the stress adaptation machinery, including hormonal control of root development (improving length and branching), protection of the photosynthetic system (improving quantum yield of photosystem II) and regulation of ion homeostasis (improving the K+:Na+ ratio in leaves and roots). To our knowledge OP is one of the few known molecules that at micromolar concentrations manifests a dual function as growth enhancer and salt stress protectant. Therefore, OP can be used as new inducer of stress tolerance to better understand molecular and physiological stress adaptation paths in plants and to design new products to improve crop performance under suboptimal growth conditions.